2017
DOI: 10.1515/cpp-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

EASE: Examination of Anomalous Self-Experience

Abstract: #Źródło: Parnas J et al. EASE: examination of anomalous self-experience. Psychopathology, 2005, 38.5: 236-258.S. Użycie skali EASE w badaniach naukowych wymaga pisemnej zgody autora skali (Josef Parnas, e-mail: jpa@cfs.ku.dk) StreszczenieSkala EASE jest listą objawów do częściowo ustrukturalizowanego fenomenologicznego badania subiektywnych lub empirycznych nieprawidłowości (anomalii), które można uznać za zaburzenia podstawowej, "minimalnej" samoświadomości. EASE opracowana została na podstawie samoopisów otr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0
12

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 28 publications
0
53
0
12
Order By: Relevance
“…The occurrence of anomalous self-experiences is common in patients with schizophrenia (21). A validated measure of this is presented in the Examination of Anomalous Self-Experience (EASE) (22), which also includes a number of body-related items ('anomalous bodily experiences'), for example motor disturbances or morphological changes. Motor disturbances comprise experiences of interference with the intended movements (or speech), of impediment or complete blockage of intended movements, sudden feeling of paresis of the arm or leg, or de-automation of everyday movements that have previously been performed automatically.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of anomalous self-experiences is common in patients with schizophrenia (21). A validated measure of this is presented in the Examination of Anomalous Self-Experience (EASE) (22), which also includes a number of body-related items ('anomalous bodily experiences'), for example motor disturbances or morphological changes. Motor disturbances comprise experiences of interference with the intended movements (or speech), of impediment or complete blockage of intended movements, sudden feeling of paresis of the arm or leg, or de-automation of everyday movements that have previously been performed automatically.…”
Section: Introductionmentioning
confidence: 99%
“…The Examination of Anomalous Self-Experience (EASE) (Parnas et al, 2005) aims to assess self-disorder experiences through a clinical interview and a rating on a descriptive-psychopathological checklist of 57 items. All items are rated on a 4-point Likert scale (0¼absent, 1¼questionably present, 2¼ present [mild], 4¼present [moderate], and 5¼present [severe]).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the truly core schizotypal personality abnormalities which concern the self-and reality awareness (Parnas et al, 2005) would factor-load on the other two subscales (Cognitive-Perceptual and Interpersonal). In particular, as Sass (2011) has interestingly Table 3 Cronbach's Alpha coefficients of the SPQ-B and dimensions in the three-factor solution (Raine and Benishay, 1995) and in the two-factor solution (Aycicegi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these studies have shown that schizophrenia patients are not psychotic for most of the time of their illness course, and instead are often able to perceive, communicate and cope with a broad range of subjective disturbances and deficits of thought, perception, mood, emotional resonance, vital drive, language, psychomotor activity, volition, and bodily sensations which represent their fundamental psychopathological vulnerability susceptible to transitions toward first-rank symptoms and other full-blown psychotic phenomena. The application of instruments like the SPQ-B is far less complex to grasp by the individual than an interview with the Bonn Scale for the Assessment of Basic Symptoms (BSABS) (Gross et al, 1987) or the EASE (Examination of Anomalous Self-experience) (Freedman and Chapman, 1973;Parnas et al, 2005) which are usually successfully administered in schizophrenia patients even over several years of follow up of their illness course. Therefore, schizophrenia patients are also expected to provide highly reliable and insightful self-reports of SPD features as assessed with the SPQ-B.…”
Section: Discussionmentioning
confidence: 99%